Membangun Kesadaran Hukum Masyarakat Terhadap Hukum Hibah, Wasiat, Dan Waris Berdasarkan Kompilasi Hukum Islam - Baihaki , Ahmad; Chandra Prasetya, Januanto Kawita; Nurani, Dwi Cahya; Batubara, Easter Aprilina; Assalwa, Meitsa Ullinuha (Abdi Bhara, 2024)
Grants, wills, and inheritance are important instruments in Islamic law that govern the transfer of treasure from one individual to another, both during life and after death. The Compilation of Islamic Law in Indonesia provides a specific legal framework to manage these three concepts in accordance with Sharia principles. However, the implementation of grants, wills, and inheritance distribution often becomes a legal problem in the community because the implementation is carried out without proper knowledge based on the provisions of Islamic law or The Compilation of Islamic Law. To prevent misunderstandings regarding this matter, legal education was held for the community in Lubang Buaya Village, Setu District, Bekasi Regency. This legal education activity has provided understanding and awareness of the legal regulations regarding gifts, wills and inheritance in the Compilation of Islamic Law as well as providing solutions to various legal problems that often occur in society.